Should there be a visual standard for ophthalmologists and other surgeons?. Issue 1016 (14th June 2010) - Wong, Newton W K; Stokes, John; Foss, Alexander J E; McGraw, Paul V
Abstract : A number of professions have a visual standard but there is no standard for surgeons, including surgeons such as ophthalmologists who operate with the aid of a microscope. We review which professions do have a visual standard, the evidence addressing the issue of a visual standard in medicine and surgery, and an international survey of what visual standards other countries apply to ophthalmologists, and performed a survey of the views of the member of the British Royal College of Ophthalmologists. A number of professions, where public safety is an issue, do have a visual standard without compelling supporting evidence. By contrast, all but two countries do not have a visual standard for their ophthalmic surgeons. The survey of members of the British Royal College of Ophthalmologists supported the adoption of such a standard, which would include minimum requirements for both visual acuity and stereoacuity. Good vision is clearly essential for ophthalmologists, as well as for other surgeons and practioners of some other branches of medicine. While there is no evidence to support a specific visual standard, we conclude that one should be adopted until there is definitive evidence to settle the issue on the basis of the precautionary principle as patient safety is involved.